2015
DOI: 10.1021/la504399e
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelasticity of Smart Fluids Based on Wormlike Surfactant Micelles and Oppositely Charged Magnetic Particles

Abstract: Novel viscoelastic smart suspensions based on cationic wormlike micelles (WLMs) of erucylbis(hydroxyethyl)methylammonium chloride and oppositely charged submicron magnetite particles in the presence of added low molecular weight salt were prepared and investigated. The suspensions demonstrate remarkable stability against sedimentation, which can be due to the incorporation of particles into the network of entangled WLMs by linking to energetically unfavorable micellar end-caps. Added particles enhance signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 41 publications
6
76
0
3
Order By: Relevance
“…In the absence of magnetic field, the SMN with 3 vol % magnetite has almost the same value of storage modulus G as the sample with 0.2 vol % magnetite (data not shown here), which is expected, because at these concentrations, the dependencies of G and G on the content of the particles level off [15]. However, in 1 T magnetic field the values of G and G for the SMN sample with 3 vol % of particles are by two orders of magnitude higher than for the sample with 0.2 vol % of particles.…”
Section: Resultssupporting
confidence: 60%
See 4 more Smart Citations
“…In the absence of magnetic field, the SMN with 3 vol % magnetite has almost the same value of storage modulus G as the sample with 0.2 vol % magnetite (data not shown here), which is expected, because at these concentrations, the dependencies of G and G on the content of the particles level off [15]. However, in 1 T magnetic field the values of G and G for the SMN sample with 3 vol % of particles are by two orders of magnitude higher than for the sample with 0.2 vol % of particles.…”
Section: Resultssupporting
confidence: 60%
“…By scanning electron microscopy, it was shown that the average diameter of the particles is about 250 nm [15]. These particles possess ferrimagnetic properties [23], their saturation magnetization is 100 emu/g, the residual magnetization is 19 emu/g, and the coercive force -95 Oe [15]. Dispersions of these magnetic particles in WLM viscoelastic solutions were prepared following a previously developed procedure [15].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations